An adaptive gridding technique for conservation laws on complex domains - Boden, E. P. (Cranfield University, 1997)
Obtaining accurate solutions to flows that involve discontinuous features still re- mains one of the most difficult tasks in computational fluid dynamics today. Some discontinuous features, such as shear waves and material interfaces, are quite deli- cate, yet they have a profound effect on the rest of the flow field. The accuracy of the numerical scheme and the quality of the grid discretisation of the flow domain, are both critical when computing multi-dimensional discontinuous solutions. Here, the second order WAF scheme is used in conjuction with an adaptive grid algorithm, which is able to automatically modify the grid in regions of discontinuous features and solid boundaries. The grid algorithm is a combination of two successful ap- proaches, namely Chimera and Cartesian grid Adaptive Mesh Refinement (AMR). The Chimera approach is able to accurately represent non-Cartesian boundaries, whilst the AMR approach yields significant savings in memory storage and cPu time. The combined algorithm has been thoroughly validated for convection test problems in gas dynamics. The computed solutions compare well with other numerical and experimental results. These tests have also been used to assess the efficiency of the grid adaption algorithms. Finally, the approach is applied to axi-symmetric, two- dimensional, two-phase, reactive flows in the context of internal ballistics problems. Again, the computed results are compared with other numerical and experimental results.